Evaluasi Implementasi Kebijakan Pencegahan Perkawinan Anak Di Kabupaten Malang - Yusroni, Ahmad Yusroni (Universitas Teknologi Surabaya, 2025)
This study aims to evaluate the implementation of the child marriage prevention policy in Malang District. The urgency of this research is that in recent years Malang District has been one of the districts in East Java Province with the highest number of child marriage cases. However, one of the interesting things is that there was a decrease in the number of cases from 2020 to 2024 even though it was not significant, this shows that there are good implications from the implementation of several policies and programs by the local government. The results showed that the Malang District government through DP3A has implemented several policies to overcome the problem of child marriage. Such as the policy of establishing a Village Child Protection Commission (KPAD), Simultaneous Movement Module Program, Socialization of Adolescent Reproductive Health Education for each junior / MTs and SMA / MA / SMK, and selection of peer counselors. Some of the programs that have been implemented have not been optimal, even so the program has had a positive impact on preventing child marriage in Malang District.